2020
DOI: 10.7554/elife.55335
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal and cortical mechanisms at retrieval explain variability in episodic remembering in older adults

Abstract: Age-related episodic memory decline is characterized by striking heterogeneity across individuals. Hippocampal pattern completion is a fundamental process supporting episodic memory. Yet, the degree to which this mechanism is impaired with age, and contributes to variability in episodic memory, remains unclear. We combine univariate and multivariate analyses of fMRI data from a large cohort of cognitively normal older adults (N=100) to measure hippocampal activity and cortical reinstatement during retrieval of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
43
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 81 publications
12
43
0
Order By: Relevance
“…Specifically, both single-item and set-level ERS was associated with successful remembering within the ventral visual stream and frontal cortices (Ritchie et al 2013). This finding is supported a more recent study by Trelle et al (2020) who also found that ventral temporal cortex ERS was predictive of veridical memory retrieval. Accordingly, research suggests that the similarity in neural patterns within ventral visual cortices across memory phases play a critical role in memory success in younger adults.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Specifically, both single-item and set-level ERS was associated with successful remembering within the ventral visual stream and frontal cortices (Ritchie et al 2013). This finding is supported a more recent study by Trelle et al (2020) who also found that ventral temporal cortex ERS was predictive of veridical memory retrieval. Accordingly, research suggests that the similarity in neural patterns within ventral visual cortices across memory phases play a critical role in memory success in younger adults.…”
Section: Introductionsupporting
confidence: 90%
“…For example, it is possible that older adults do not store, and thus do not have available as many or as high-quality, encoding-related details for retrieval compared to their younger counterparts (Dennis, Bowman, et al, 2014;Hill et al, 2021). It is also possible that older adults have such details stored in their memory, but fail to reactivate these memory traces at the time of retrieval (Trelle et al, 2020;Naspi et al, 2021). Either possibility would result in overall reduce similarity between neural patterns within occipital cortices across encoding and retrieval.…”
Section: Age Deficits In Ersmentioning
confidence: 99%
“…In this study, the older participants showed a weaker communication of brain areas when compared with those used by the younger ones; however, the former recruited different brain areas to compensate (McIntosh et al, 1999 ; Cabeza et al, 2002 ). These effects are attributed to some class of compensatory activity, supporting some reorganization of the aged brain that leads to “younger” cognitive abilities (Ming and Song, 2005 ; Glisky, 2007 ; Trelle et al, 2020 ; Katsumi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Why is this the case? Previous work has investigated how specific neural measures, mostly involving the hippocampus or cortico-hippocampus networks, are correlated with trait-level variations in various forms of LTM (e.g., semantic and topographic memory: Trelle et al, 2020;Sormaz et al, 2017; associative memory: Touroutoglou, Andreano, Barrett, & Dickerson, 2015; free recall: Wang et al, 2010;autobiographical memory: Sheldon, Farb, Palombo, & Levine, 2016; source memory: Sneve et al, 2017). Moving beyond correlation-based analysis, recent work has started to conduct out-of-sample prediction of individual differences in LTM (e.g., reading recall: Jangraw et al, 2018; item memory and spatial memory: Persson, Stening, Nordin, & SĂśderlund, 2018).…”
Section: Introductionmentioning
confidence: 99%